Influence of eye movements, auditory perception, and phonemic awareness in the reading process - Megino-Elvira, Laura; Martín-Lobo, Pilar; Vergara-Moragues, Esperanza (The Journal of Educational Research, 2017)
The authors' aim was to analyze the relationship of eye movements, auditory perception, and phonemic awareness with the reading process. The instruments used were the King-Devick Test (saccade eye movements), the PAF test (auditory perception), the PFC (phonemic awareness), the PROLEC-R (lexical process), the Canals reading speed test, and the ACL-1 (reading comprehension). The sample was composed of 52 first-year primary school pupils. After the correlational analysis, results indicate that all of these factors correlate in reading (lexical process, speed, and word comprehension). Moreover, the nonparametric Mann-Whitney U test reveals that children with saccade eye movements and auditory perception problems obtain lower reading levels. In addition, children with lexical problems obtain a lower level of phonemic awareness. Given the importance of these variables, the authors conclude with a proposal of neuropsychological activities to improve reading skills.
Keywords: auditory perception; eye movements; learning; phonemic awareness; reading; JCR; Scopus